Relaxing Effects of Paracetamol on Uterine Spontaneous Contraction in Rats in Vitro - Ercan, Zubeyde; Zorlu, Gokhan; Bulmus, Ozgur; Serhatlioglu, İhsan; Yasar, Abdullah; Kacar, Emine (My University, 2022)
Aim: Paracetamol is a commonly used drug in acute and chronic pain. It is known that paracetamol, which is a pain reliever and antipyretic drug, is safe to use during pregnancy. The aim of this study was to investigate the effects of paracetamol on the uterine smooth muscle contraction- relaxation mechanism in female rats in diestrus.Material and Methods: Wistar-albino intact female rats were used in the study. Longitudinal strips of myometrium obtained from animals at the diestroeus stage. Stripes were suspended in an isolated organ bath containing crebs solution under 1 g passive tension. After the regulation period, paracetamol were added non-cumulatively at 1000?M and 2000?M concentrations. Before and after the application, the area under the curve (AUC) and peak to peak (p-p) values were normalized as % change.Results: Paracetamol caused a statistically significant decrease in p-p and area under the curve parameters of spontaneous uterine contractions at 1000 and 2000 ?M doses (p <0.001).Conclusion: Paracetamol causes uterine relaxation by inhibiting uterine contraction. This effect should be taken into account in clinical use.
Keywords: Uterus; Rat; Isometric Contraction; Paracetamol